Struktur Sosial Masyarakat Nelayan Pesisir di Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Salsabila Zahri Sativa; Wasiyem Wasiyem; Nabila Fitri; Suci Ramadhani Rangkuti; Rahmayani Rahmayani; Marwah Naila Maharani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The purpose of this study was to determine the social structure in the lives of Coastal Fishermen in Pantai Cermin District, Serdang Bedagai Village. This type of research is Qualitative research. Data collection techniques are observation, interviews, to collect the data needed are primary and secondary data. The number of informants in this study was 10 people who were determined directly. The data that has been collected was analyzed descriptively qualitatively. From the results of the data analysis, conclusions were then drawn. The conclusion in this study is the social structure of the Coastal Fishermen Community in Pantai Cermin District, Serdang Bedagai Regency, namely divided into 3 layers, namely: Toke (boss), Tekong, and fishermen, workers or members This stratification of the fishing community is formed on the basis of ownership or control of capital and means of production. The social structure in the fishing community in Pantai Cermin District is open both vertically and horizontally. The working relationship in fishing activities in Pantai Cermin District is a mutually beneficial cooperative relationship.